The role of work in suicidal behavior - uncovering priorities for research and prevention - Birgit A Greiner; Ella Arensman (Nordic Association of Occupational Safety and Health (NOROSH), 2022)
More than 700 000 people die by suicide each year, and many more engage in suicide attempts and experience a mental disorder. Suicides particularly affect the working age population. It is the fourth leading cause for death in young people aged 15-29; more than half of global suicides (58%) in 2019 occurred before the age of 50 years (1). This topic is gaining attention in workplace settings throughout the world. The World Health Organization estimated that in a company of 1000 employees, 200-300 workers will suffer from a serious mental health problem in any given year, one worker will die by suicide every ten years, and for every employee who dies by suicide, another 10-20 will make a suicide attempt. Recent epidemiological research indicates an increasing trend in workplace related suicides (2). There is meta-analytical evidence indicating workplace settings associated with suicide risk, especially among people working in personal services, such as the health, construction and production, and agricultural sectors. Elementary workers had the highest suicide risk, which reflects the general finding of a gradient with the lowest skilled occupations experiencing a higher risk than highly skilled workers (3). Work-related suicide came to the attention of the wider public with the extensive media coverage of a cluster of 43 suicides in one company, France Telecom (4), and another cluster of 18 completed and attempted suicides within one year in the Chinese company, Foxconn (5). Waters et al (6) suggested that the stressful working conditions and poor management at France Telecom contributed to these tragic cases. The cluster involved cases including persons who took their lives in their workplace location, which further underlines a link between the work setting and suicide (7). The suicide cluster involving employees from France Telecom culminated in a court case and sentencing of members of France Telecom senior management (8). While the sensationalized media coverage of these two cases sparked wide criticism in relation to inappropriate mass media coverage potentially leading to copycat suicides in the respective organizations (5), the fundamental question remains: can work contribute to people taking their own lives? Is it that simple? The role of employment and unemployment in suicide Historical research had pursued the issue of the work-relatedness of suicide much earlier under the notion that non-work can make people take their own lives. The French Sociologist Émile Durkheim explained suicide in the societal context rather than by solely individual factors. For example, major societal changes, such as economic recession and loss of work, can be important contributors to a so-called "anomic suicide" (9). The suicide-unemployment association has been discussed by academics since the publication of Durkheim's classic study over 100 years ago, which concluded that unemployment increased social isolation, which then exacerbated the risk of suicide. This discussion has been rekindled by the recent COVID-related losses of jobs and economic recessions in some countries (10). Recently published systematic reviews documented increased suicide risk among the unemployed even after adjustment for pre-unemployment mental health (11,12), with a particular high risk among those in long-term unemployment (13); unemployment also increases the risk of suicide attempts and suicidal ideation (12). Can one conclude that work is good for individuals and may even protect against suicide and mental health problems? Can work give a 'lifeline' and help people to stay connected to life? The answer may be that it depends on the job. Whereas employment in general is associated with a decreased risk of suicidal behavior compared to unemployment, employment in jobs associated with adverse working conditions may be a risk factor for suicidal behavior, as indicated by evidence on the association between specific psychosocial work risks and suicide. Psychosocial work risks associated with suicidal behavior There has been a recent influx of methodologically sound studies, including large cohorts with a long follow-up time showing that specific psychosocial work factors are associated with a higher suicidal behavior risk. A systematic review of 22 studies demonstrated that exposure to psychosocial job stressors was associated with elevated risk of suicide ideation, attempts and death (14). Especially lack of job control and social support from supervisors and colleagues for both genders and high job demands among males has been associated with an increased suicide risk (9). Recent studies also indicated increased risks for suicide death among those exposed to sexual harassment [hazard ratio (HR) 2.82, 95% confidence interval (CI) 1.4 -5.34] (15), long working hours, ie, 45-52 weekly hours (HR 3.89, 95% CI 1.06-14.29) and >52 hours (HR 3.74, 95% CI 1.03-13.64) (16), job strain (a combination of high demands and low control) (HR 1.28, 95% CI 1.09-1.51 among men and HR 1.35, 95% CI 1.03-1.77 among women) and iso-strain (a combination of high demands, low control and low social support) (HR 1.29, 95% CI 1.09-1.53 among men and HR 1.36, 95% CI 1.04-1.78 among women) (17), workplace bullying mainly among men (HR 2.92, 95% CI 1.74-4.91) (18) and a decreased risk for those in 'active jobs' (high control/high demands) (HR 0.64, 95% Cl 0.60-0.70) (19). Notably, most of these recent longitudinal studies adjusted the effect measures for a range of sociodemographics, personal risk factors and baseline mental health, thereby investigating the independent contribution of working conditions associated with suicide. While some of the risks are substantially elevated, some are also imprecise estimates and based on small case numbers as death by suicide is a rare event. Results are inconclusive in relation to gender differences due to even smaller case numbers among women, as suicide is more common among men. With increasing research in this area, meta-analyses providing more precise pooled estimates of the exposure to specific psychosocial work exposures may become feasible in the future with detailed sub-group analyses. Theoretical challenges While research into the role of specific job stressors on suicidal behavior can be considered in its infancy, the growing body of epidemiological evidence has the potential to scientifically establish poor psychosocial working conditions as a risk factor among the pool of other well-known risks factors for suicidal behavior. Suicidal behavior is complex and cannot be explained by one causal factor. Suicide research usually differentiates between underlying risk factors and precipitating events in the immediate environment triggering suicidal behavior. A model to explain the complexity is the Diathesis-Stress Model of suicide. It defines stressors as the recurrence of depressed mood or psychotic symptoms within the course of a psychiatric disorder or a negative stressful life event, such as losing one's job or the death of family member or friend. Such a stressor may lead to the subjective experience of depressed mood and suicidal thoughts, which may induce suicidal ideation and increase the risk of a suicidal crisis via interaction with a trait disposition, such as hopelessness and neuroticism (20, 21). The addition of specific occupational characteristics to the canon of preconditions is relatively novel and requires the expansion of theoretical frameworks to explain the mechanisms that link workplace factors among other contributors to suicidal behavior. In suicide research, workplace factors have been generally conceptualized as factors immediately precipitating suicidal behavior, eg, in the context of job loss, or traumatic work events such as violence (20, 22). The theoretical integration of chronic exposure to work stressors as underlying risk factor with their accumulative impact on vulnerability and onset / aggravation of mental health problems would create an opportunity to integrate the scientific evidence of two academic disciplines: psychiatry and occupational epidemiology. The first models have now been published with integration of the "interpersonal-psychological theory of suicide" and the "psychache theory of suicide" with integration of work factors (23).